Estructura horizontal y potencial volumétrico de especies comerciales de un bosque de colina baja de la comunidad nativa Luciana, distrito de Requena, Loreto. 2023 - Luna Vela, Jose Joel (2024)
The study was carried out in the Colina Baja forest, located in the Luciana native community, in order to analyze the horizontal structure and timber volume of commercial forest species. A total of 934 trees were recorded, distributed in 22 species, 21 genera and 11 families. The Fabaceae family stands out for having the largest five genera (23.8%) and five species (22.7%). Among the most common species are C. estrellensis (52.7%), O. platyspermum (21.2%), E. coriacea (27.4%), O. amazonica (19.6%), C. glabrum (19.0%) and B. utile sp. (18.5%). In terms of volume, C. estrellensis has the highest contribution with 0.7 m³/ha (19.6%), followed by O. platyspermum with 0.4 m³/ha (11.0%) and V. duckei with 0.3 m³/ha (8.3%). The total timber volume reported for the forest is 3.8 m³/ha. It is recommended that the forest be enriched with the commercial species C. estrellensis due to its high value and commercial volume, in order to maximize the economic benefits of the Colina Baja forest.